Linking International Faculty Integration to International Academic Impact: The Moderating Role of Institutional Digitization Level in Chinese Universities - Wenji Fan; Shangwei Fang (Education Sciences)
The introduction of international faculties is a crucial strategy in enhancing the talent pool of Chinese universities, yet its impact on scientific research development remains underexplored. This study investigates how the presence of an international faculty influences the international academic impact of 128 “Double First-class” Chinese universities from 2011 to 2020. Using benchmark regression models alongside endogeneity and robustness tests, the analysis incorporates moderating effects and heterogeneity to examine underlying mechanisms. The results indicate that the introduction of foreign faculty significantly enhances the international academic impact of these institutions. Furthermore, the scientific and technological human capital of a foreign faculty plays a key role in this effect. This study also finds that the universities’ level of digitalization significantly moderates the relationship between international faculty presence and academic impact. Additionally, the impact varies across regions and development levels, highlighting heterogeneity in outcomes. These findings suggest that Chinese universities should strategically strengthen the recruitment of international faculties, carefully assess their expertise, and leverage digital capabilities to maximize academic benefits. This research provides empirical evidence on the value of international faculties in advancing the global academic standing of Chinese higher education institutions.